2019
DOI: 10.1016/s0140-6736(19)31133-x
|View full text |Cite
|
Sign up to set email alerts
|

Ending the neglect of global oral health: time for radical action

Abstract: 75Oral diseases are a major global public health problem affecting over 3.5 billion people. 76Dentistry however has failed to tackle this problem. A fundamentally different approach is 77 now needed. In this second paper on oral health, we present a critique of dentistry 78 highlighting its key limitations and the urgent need for system reform. In high-income 79 countries (HIC) the current treatment-dominated, increasingly high-tech, interventionist and 80 specialised approach, is failing to tackle the underly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
640
0
29

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 589 publications
(686 citation statements)
references
References 77 publications
17
640
0
29
Order By: Relevance
“…Yet this approach is unlikely to be achieved while treatment is prioritised before prevention. Our study lends weight to the growing call for radical reforms to the current model of oral health [49,50]. Watt et al and Cohen et al have indicated that the present treatment focus on individuals is harming those that are most vulnerable and unable to afford care [49,50].…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Yet this approach is unlikely to be achieved while treatment is prioritised before prevention. Our study lends weight to the growing call for radical reforms to the current model of oral health [49,50]. Watt et al and Cohen et al have indicated that the present treatment focus on individuals is harming those that are most vulnerable and unable to afford care [49,50].…”
Section: Discussionsupporting
confidence: 56%
“…Our study lends weight to the growing call for radical reforms to the current model of oral health [49,50]. Watt et al and Cohen et al have indicated that the present treatment focus on individuals is harming those that are most vulnerable and unable to afford care [49,50]. Indeed, all our participants reported poor oral health as adults and within the wider study population, 75.5% of participants had self-reported decayed, missing or filled teeth [24].…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Recently, there has been a worldwide shift in certain educational components within healthcare fields . This is due in part to the newfound understanding of the role that social components—such as empathy and intersectionality—play in the provision of healthcare, including dental care .…”
Section: Introductionmentioning
confidence: 99%
“…Dental diseases are good examples of complex diseases which are associated with a range of poor health outcomes and are hypothesized to be both a cause and consequence of ill health 1 but the limitations of conventional epidemiological methods do not exclude confounded association. In the context of recent calls to prioritize prevention and early interventions, address the global health problem of dental diseases and overcome isolation between dentistry and medicine 2,3 , there is a need to locate dental diseases in the context of causal flow through the human phenome. Conversely, lipid biomarkers such as low-density lipoprotein cholesterol (LDL-C) are good examples of traits which are known to have effects on human health including cardiovascular disease 4,5 and may act as a positive control for contemporary epidemiological methods which aim to identify causal relationships.…”
Section: Introductionmentioning
confidence: 99%